Snowball Earth climate dynamics and Cryogenian geology-geobiology - Hoffman, Paul F.; Abbot, Dorian S.; Ashkenazy, Yosef; Benn, Douglas I.; Brocks, Jochen J.; Cohen, Phoebe A.; Cox, Grant M.; Creveling, Jessica R.; Donnadieu, Yannick; Erwin, Douglas H.; Fairchild, Ian J.; Ferreira, David; et al. (Science Advances, 2017)
G.R. was supported by CNRS funding through the ECLIPSE program. B.E.J.R. was supported by NSF grant AGS-1455071. A.V. was supported by the German Federal Ministry of Education and Research (BMBF) and Research for Sustainable Development (FONA) (www.fona.de) under grant 01LK1509A. S.G.W. was supported by NSF grant ANT-1142963. Geological evidence indicates that grounded ice sheets reached sea level at all latitudes during two long-lived Cryogenian (58 and ≥5 My) glaciations. Combined uranium-lead and rhenium-osmium dating suggests that the older (Sturtian) glacial onset and both terminations were globally synchronous. Geochemical data imply that CO2 was 102 PAL (present atmospheric level) at the younger termination, consistent with a global ice cover. Sturtian glaciation followed breakup of a tropical supercontinent, and its onset coincided with the equatorial emplacement of a large igneous province. Modeling shows that the small thermal inertia of a globally frozen surface reverses the annual mean tropical atmospheric circulation, producing an equatorial desert and net snow and frost accumulation elsewhere. Oceanic ice thickens, forming a sea glacier that flows gravitationally toward the equator, sustained by the hydrologic cycle and by basal freezing and melting. Tropical ice sheets flow faster as CO2 rises but lose mass and become sensitive to orbital changes. Equatorial dust accumulation engenders supraglacial oligotrophic meltwater ecosystems, favorable for cyanobacteria and certain eukaryotes. Meltwater flushing through cracks enables organic burial and submarine deposition of airborne volcanic ash. The subglacial ocean is turbulent and well mixed, in response to geothermal heating and heat loss through the ice cover, increasing with latitude. Terminal carbonate deposits, unique to Cryogenian glaciations, are products of intense weathering and ocean stratification. Whole-ocean warming and collapsing peripheral bulges allow marine coastal flooding to continue long after ice-sheet disappearance. The ...